Seismic Analysis of Symmetric and Asymmetric Buildings - Lia Balanchivadze; George Maisuradze; Archil Chikhladze (Scientific Research and Experimental Development, 2025)
In the paper, the inelastic seismic behavior of symmetric and asymmetric single-story and multi-story buildings is studied using a numerical example. The impact of hail on buildings is analyzed. The results of seismic reports for buildings with symmetric and asymmetric plan shapes are compared. A single-story building with three degrees of freedom is modeled in two ways - in one case, the column is replaced by springs, and in the other case, the actual cross-section is taken. In addition, an 11-story building is calculated, which in one case has the same eccentricity on all floors (uniform eccentricity) and in the other case has variable eccentricity by floors. The seismic report was based on the El Centro 1940 N-S earthquake record